2009
DOI: 10.1159/000264671
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Asymmetric Dimethylarginine Levels in Primary Dysmenorrhea

Abstract: Background: Primary dysmenorrhea is a common disorder among young women, and uterine ischemia plays an important role in pelvic pain. Asymmetric dimethylarginine (ADMA) is accepted as a strong marker of endothelial dysfunction. Objective: To investigate the role of ADMA in primary dysmenorrhea. Methods: Thirty-three patients with primary dysmenorrhea and 29 healthy controls were evaluated in a hospital outpatient clinic-based study. Secondary causes of dysmenorrhea had been ruled out in each patient. LDL chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Here, we summarize studies previously reviewed [25,42,43,44,45,46] and highlight new data documenting associations between elevated ADMA levels and clinical conditions in specific patient populations. As shown in Table 1, elevated circulating ADMA concentrations have been described in a variety of diseases across different age and sex groups [3,42,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90]. Differences in ADMA concentrations between sexes are small [33], whereas difference between different age groups do exist.…”
Section: Clinical Conditions Associated With Elevated Adma and Sdmmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we summarize studies previously reviewed [25,42,43,44,45,46] and highlight new data documenting associations between elevated ADMA levels and clinical conditions in specific patient populations. As shown in Table 1, elevated circulating ADMA concentrations have been described in a variety of diseases across different age and sex groups [3,42,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90]. Differences in ADMA concentrations between sexes are small [33], whereas difference between different age groups do exist.…”
Section: Clinical Conditions Associated With Elevated Adma and Sdmmentioning
confidence: 99%
“…Many diseases affect both women and men alike; however, some diseases occurring at a higher frequency in women (e.g., systemic lupus erythematous) or affecting only women (e.g., preeclampsia [52], polycystic ovary syndrome [67], and primary dysmenorrhea [73]) have been linked with elevated ADMA concentrations. Additionally, some pediatric diseases such as prematurity [64], congenital urea cycle enzyme defects [69], and transient tachypnea in newborns [88] are associated with elevated plasma ADMA levels.…”
Section: Clinical Conditions Associated With Elevated Adma and Sdmmentioning
confidence: 99%
“…In another study, the levels of MDA and interleukin-6 were elevated in patients with primary dysmenorrhea (Yeh et al, 2004). In a study by Akdemir et al (2010), levels of serum nitric oxide and asymmetric dimethylarginine (as a marker of endothelial dysfunction and nitrogen radicals) were observed to be significantly higher in patients with primary dysmenorrhea than in the control group. Taken together, these results indicated reduced antioxidant activity in primary dysmenorrhea.…”
Section: Discussionmentioning
confidence: 90%
“…Endothelial dysfunction was a very important reason for headache (chronic migraine) [28] and dysmenorrheal [29]. At present, many data [30]–[32] suggested that chronic migraine and cardiovascular disease had the same pathophysiological mechanisms as follows: abnormal control of systemic vascular tone, alterations in systemic arterial structure and function and impaired ability to repair systemic endothelial injury.…”
Section: Resultsmentioning
confidence: 99%